A Systematic Map of Inclusion, Equity and Diversity in Science Communication Research: Do We Practice what We Preach? - Judd, Karina; McKinnon, Merryn (Frontiers in Communication, 2021)
Effective engagement with diverse stakeholders, combating misinformation and encouraging wider participation in science is core to science communication practice, and comprises much of the current focus of research in the discipline. Global events, such as the COVID-19 pandemic, have clearly shown that social inequalities also manifest within communication structures, including those of science communication. Practices which are inclusive of diverse audiences are key if we wish to engage diverse audiences in finding solutions to societal issues. Yet there is little available evidence to show which diverse, marginalised and/or excluded groups are being engaged within science communication, and via what means. This paper develops a systematic map of academic literature spanning 40 years to provide a preliminary evidence base of how diversity and inclusion within science communication research and practice is conceived and implemented. Although the discipline has shown an increased focus within the last five years, science communication must evolve further in order to develop a robust evidence base for understanding what constitutes inclusive science communication in both theory and practice.